Muitinės audito organizavimas ir jo tobulinimo galimybės - Adomavičiūtė, Danutė; Mackevičius, Jonas (Information & Media, 2012)
Straipsnyje nagrinėjama muitinės audito reikšmė, tikslai ir jo vieta audito sistemoje. Muitinės auditas apibūdinamas kaip procesas, kurio metu muitinės pareigūnai atlieka ūkio subjekto veiklos vertinimą, tikrindami muitinės deklaracijose esančios informacijos teisingumą. Pabrėžiami muitinės audito bendri bruožai ir esminiai skirtumai, palyginti su finansinių ataskaitų, valdymo, veiklos ir kitomis audito rūšimis. Tiriamos muitinės audito sritys: importo, eksporto, tranzito ir kitos muitinės procedūros. Akcentuojamas audito proceso nuoseklumas; nagrinėjami pagrindiniai muitinės audito etapai: 1) planavimo ir atrankos, 2) pasirengimo, 3) vykdymo, 4) rezultatų įforminimo, 5) peržiūros. Nagrinėjant muitinės audito tobulinimo galimybes ypač pabrėžiamas strateginio audito taikymas vertinant verslo įmonių rizikas. Reikšminiai žodžiai: muitinė, muitinės auditas, audito sritys, audito atlikimo etapai, tobulinimo galimybės. Organization of Customs Audit and Possibilities of Development Danutė Adomavičiūtė, Jonas Mackevičius Summary The main strategic objective of Lithuanian customs is the defence of the market and society in the field of the foreign trade while implementing the policy of the European Community’s taxes and trade. To achieve this objective, one of the main challenges is to implement measures related to the safety and security of the international trade supply and to prevent terrorism, smuggling, organised crime and other criminalities. The focus is placed on the application of the audit-based control measures in order to overcome the logistical barriers that inevitably arise in the process of international trade. The customs audit is of a great importance in the process of the customs inspection. The control based on the methods of the customs audit assures better opportunities of anti-breaches. Moreover, a faster flow of goods traffic at the external border of the European Union is assured while carrying out most inspections at the companies’ residences. Therefore, it is important to improve the customs audit, combining this process with the changing business environment. This also has to do with the ongoing market processes. Recently, the customs of the EUcountries have begun appreciating the activities of the business enterprises, seeking to gain the status of the authorised economic operator (AEO). The customs audit is a highly effective tool ensuring the business enterprise activities’ assessment in the financial, legal and security aspects. The main objectives of the customs audit are the following: 1) to check the data accuracy and comprehensiveness indicated in the customs declarations, 2) to define the breaches on the basis of which duties and other taxes are being counted, and errors of the data in the documents provided by the importers and exporters as well as other persons accepting the customs obligations, 3) to evaluate the entities’ activities and compliance with the requirements. A comparison of all types of the audit shows that the customs audit has many features in common with the other types of the audit. There is a special correlation between the customs audit and financial, operational and management audit. The customs audit, having common features with other types of the audit, has also some differences. Its different goal has its own special features. Customs procedures, goods’ customs value, goods’ classification, origin and other things can become the inspected areas of business enterprises’ activities and the items to be assessed. Customs’ conducted process of the business enterprise activities assessment has a number of procedural aspects arising from the activity’s particularity. The assessment of business enterprises’ activities in Lithuanian customs is carried out taking into consideration the issuing/non-issuing of the AEO status when the customs audit assesses the activities of the economic operator and its compliance with the established criteria.